2021
DOI: 10.1016/j.molcel.2021.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Rapid characterization of spike variants via mammalian cell surface display

Abstract: The SARS-CoV-2 spike protein is a critical component of vaccines and a target for neutralizing monoclonal antibodies (nAbs). Spike is also undergoing immunogenic selection with variants that increase infectivity and partially escape convalescent plasma. Here, we describe Spike Display, a high-throughput platform to rapidly characterize glycosylated spike ectodomains across multiple coronavirus-family proteins. We assayed ∼200 variant SARS-CoV-2 spikes for their expression, ACE2 binding, and recognition by 13 n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 80 publications
0
38
0
Order By: Relevance
“…Deep mutational scanning (DMS) predicts protein expression, ACE2 binding, and mAb binding [ 5 ]. The method was first deployed with yeast display libraries [ 6 ], then evolved to phage display libraries ( ) [ 7 ] and finally mammalian cell surface display [ 8 ]. nAb binding is common within the fusion peptide and in the linker region before heptad repeat (HR) region 2.…”
Section: Introductionmentioning
confidence: 99%
“…Deep mutational scanning (DMS) predicts protein expression, ACE2 binding, and mAb binding [ 5 ]. The method was first deployed with yeast display libraries [ 6 ], then evolved to phage display libraries ( ) [ 7 ] and finally mammalian cell surface display [ 8 ]. nAb binding is common within the fusion peptide and in the linker region before heptad repeat (HR) region 2.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of variants of concern (VOCs) with the enhanced transmissibility and infectivity profile including the D614G variant [54][55][56][57], B.1.1.7 (alpha) [58][59][60][61], B.1.351 (beta) [62,63], B.1.1.28/P.1 (gamma) [64], and B.1.1.427/B.1.429 (epsilon) variants [65,66] have attracted enormous attention in the scientific community and a considerable variety of the proposed mechanisms explaining functional observations from structural and biochemical perspectives. The detection of common mutational changes such as D614G, E484K, N501Y, and K417N that are shared among major circulating variants B.1.1.7, B.1.351, and B.1.1.28/P.1 indicated that these positions could be particularly critical for modulation of the SARS-CoV-2 S protein responses.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of variants of concern (VOC's) with the enhanced transmissibility and infectivity profile including D614G variant [54][55][56][57], B.1.1.7 (alpha) [58][59][60][61], B. 1.351 (beta) [62,63], B.1.1.28/P.1 (gamma) [64], and B.1.1.427/B.1.429 (epsilon) variants [65,66] revealed complex mechanisms underlying function and dynamics of the S proteins in different biological environments. Structural and biophysical studies characterized a diversity of S functional states for B.1.1.7 (B.1.1.7), B.1.351 (beta), P1 (gamma), and B.1.1.427/B.1.429 (epsilon) variants and showed that conformational plasticity of S proteins is modulated by mutations and determines the ability to evade host immunity and incur resistance to antibodies [67][68][69].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 S mutants with the enhanced infectivity profile have attracted an enormous attention in the scientific community following the evidence of the mutation enrichment via epidemiological surveillance, resulting in proliferation of experimental data and a considerable variety of the proposed mechanisms explaining functional observations. The emergence of variants of concern (VOC’s) with the enhanced transmissibility and infectivity profile including D614G variant [ 54 , 55 , 56 , 57 ], B.1.1.7 (alpha) [ 58 , 59 , 60 , 61 ], B.1.351 (beta) [ 62 , 63 ], B.1.1.28/P.1 (gamma) [ 64 ], and B.1.1.427/B.1.429 (epsilon) variants [ 65 , 66 ] revealed complex mechanisms underlying function and dynamics of the S proteins in different biological environments. Structural and biophysical studies characterized a diversity of S functional states for B.1.1.7 (B.1.1.7), B.1.351 (beta), P1 (gamma), and B.1.1.427/B.1.429 (epsilon) variants and showed that conformational plasticity of S proteins is modulated by mutations and determines the ability to evade host immunity and incur resistance to antibodies [ 67 , 68 , 69 ].…”
Section: Introductionmentioning
confidence: 99%